Meta-Synthesis: Problem-Based Learning in Improving Students' Mathematical Problem-Solving Skills - Jezlina Hamid; Arief Agoestanto; Scholastika Mariani; Isnaini Rosyida (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to analyze and synthesize various research results regarding the application of the Problem-Based Learning (PBL) model in improving students' mathematical problem-solving skills at various levels of education. The approach used is a Systematic Literature Review (SLR) with a qualitative meta-synthesis method based on guidelines (Kitchenham, 2007). The data sources were obtained from ten relevant national and international scientific articles published between 2020 and 2025. The articles used in this study were five accredited national and international journal articles obtained from Publish or Perish and Google Scholar. The meta-synthesis results show that the PBL model consistently has a positive impact on improving mathematical problem-solving skills in various learning contexts. The findings also indicate that PBL contributes to the development of students' critical, reflective, and metacognitive thinking skills. The integration of digital technologies such as GeoGebra and Teachmint has been proven to strengthen the effectiveness of PBL, while a culture-based approach through ethnomathematics increases the contextual relevance of mathematics learning. However, the effectiveness of PBL is influenced by teacher readiness, learning time constraints, and student characteristics. This study confirms that Problem-Based Learning is an effective, adaptive, and contextual learning model for developing students' higher-order thinking skills. These findings are expected to serve as a reference for educators and curriculum developers in designing more collaborative, context-based mathematics learning strategies that are in line with the spirit of the Merdeka Curriculum.